Report on the status of women (Government of Dominica RoseauDM, 1994)
Gives an overall picture of the critical issues that affect women in Dominica. Looks at the early eighties and recalls what the situation was like for women prior to the Nairobi Conference, the changes that have taken place since and some of the innovative activities and programmes that have been undertaked to advance the status of women in Dominica.
Prepared for the UN Fourth World Conference on Women, Beijing, China, 1995